THE IMPACT OF PRICE AND QUALITY PRODUCT ON CONSUMERS’ PURCHASING DECISION IN KAOS ANAK FOR KIDS’ (KAFK) CLOTHING SHOP - Immanuel Gerin Johansyah; Keni Kaniawati (SAMPURASUN, 2020)
This research reveals that there is a gap between high growth of clothing shop and decreased product buying of KAFK clothing shop. Study case has conducted on kid fashion consumer. The purpose of the research is to know whether there is a price and product quality influence in considering KAFK clothing shop consumer purchase intention. Those factors tested in this research are price and product quality as independent variable, while purchase intention as dependent variable. The research methodology is descriptive method, using data gathering from observation and questionnaire. The population is child fashion product consumer with 150 respondent research samples. The data analysis use Path Analysis. The finding of the research shows that two independent variables, which are price and product quality, are influencing in considering KAFK clothing shop consumer purchase intention.